Neuroimaging assessment of pediatric cerebral changes associated with SARS-CoV-2 infection during pregnancy - Alves de Araujo Junior, David; Motta, Felipe; Fernandes, Geraldo Magela; Castro, Maria Eduarda Canellas De; Sasaki, Lizandra Moura Paravidine; Luna, Licia Pacheco; Rodrigues, Thalys Sampaio; Kurizky, Patricia Shu; Soares, Alexandre Anderson De Sousa Munhoz; Nobrega, Otavio de Toledo; Espindola, Laila Salmen; Zaconeta, Alberto Moreno; et al. (Frontiers in Pediatrics, 2023)
SARS-CoV-2 infection and perinatal neurological outcomes are still not completely understood. However, there is recent evidence of white matter disease and impaired neurodevelopment in newborns after maternal SARS-CoV-2 infection. These appear to occur as consequence of both direct viral effects and systemic inflammatory response, with glial cells / myelin involvement. We sought to characterize consequences of the maternal and fetal inflammatory condition in the central nervous system of newborns post SARS-CoV-2 maternal infection. Methods: longitudinal prospective cohort study, from June 2020 to December 2021, with follow-up of newborns from mothers exposed or not exposed to SARS-CoV-2 infection during pregnancy. Brain analysis included cranial ultrasound scan (CUS) with grayscale, Doppler studies (color and spectral), and ultrasound-based brain elastography in specific regions of interest (ROIs): deep white matter, superficial white matter, corpus callosum, basal ganglia, and cortical grey matter. Brain elastography was used for estimation of brain parenchymal stiffness, an indirect quantifier for myelin cerebral tissue content. Results: 219 single-pregnancy children were enrolled, including 201 from mothers exposed to SARS-CoV-2 infection and 18 from unexposed controls. Neuroimaging evaluation was performed at 6 months of adjusted chronological age, and it demonstrated 18 grayscale and 21 Doppler abnormal exams. Predominant findings were hyper echogenicity of deep brain white matter and basal ganglia, and reduction in resistivity and pulsatility index of intracranial arterial flow. Anterior brain circulation (middle cerebral and pericallosal arteries) displayed wider range of flow variation than posterior circulation (basilar artery). Shear-wave US elastography analysis demonstrated reduction of stiffness values in SARS-CoV-2 exposed group at all analyzed regions of interest, especially in the deep white matter elasticity coefficients (3.98 ± 0.62) compared to control group (7.76 ± 0.77); p-value<0.001. Conclusion: This study further characterizes pediatric structural encephalic changes associated with SARS-CoV-2 infection during pregnancy. Maternal infection has shown to be related to cerebral deep white matter predominant involvement, with regional hyper echogenicity and reduction of elasticity coefficients, suggesting zonal impairment of myelin content. Morphological findings may be subtle, and functional studies such as Doppler and elastography may be a valuable tool for identifying more accurately which infants are at risk of neurological damage.